Data trust and data privacy in the COVID-19 period. (6th January 2022) - Biddle, Nicholas; Edwards, Ben; Gray, Matthew; Hiscox, Michael; McEachern, Steven; Sollis, Kate
Abstract: In this article, we focus on data trust and data privacy, and how attitudes may be changing during the COVID-19 period. On balance, it appears that Australians are more trusting of organizations with regards to data privacy and less concerned about their own personal information and data than they were prior to the spread of COVID-19. The major determinant of this change in trust with regards to data was changes in general confidence in government institutions. Despite this improvement in trust with regards to data privacy, trust levels are still low.